Measuring Religious Obligations from the Perspective of Values and Legislation - Iskandarsyah Siregar; Aziz Rahimy (Budapest International Research and Critics University, 2023)
This study embarks on an exploration to address the complex issue of defining religious obligations within the framework of Indonesian society. It is particularly important to understand these obligations in the context of Indonesia's foundational ideology, Pancasila, the foremost principle of which affirms a belief in a Single, Supreme God. Given the legal and ethical complexities involved, a juridical-normative approach is employed as the analytical lens to scrutinize and understand policy-related aspects surrounding the religious obligations in Indonesia. The juridical-normative methodology is particularly useful for unearthing and interpreting governmental policies and societal norms that influence religious adherence in the country. Although the Indonesian government does not explicitly mandate its citizens to follow only the religions it formally recognizes namely Islam, Christianity, Buddhism, and Hinduism there exists an underlying tension between formal recognition and actual practice. The findings indicate that in practice, adherents of other local belief systems such as Sunda Wiwitan, Kaharingan, and Parmalim, which have been passed down from generation to generation, often face discriminatory treatment that belies the spirit of the Pancasila's first principle. The study reveals a nuanced picture where, on the one hand, there is an officially sanctioned list of recognized religions, and on the other, a ground reality where not all spiritual paths are treated equally. This divergence between policy and practice raises questions about the extent to which Indonesia's constitutional laws and its foundational Pancasila ideology are applied uniformly across its diverse religious landscape. The study serves as a steppingstone for further dialogue and research into the complexities of religious obligations and freedoms within Indonesia, particularly in the context of its legal and ethical framework.